Announcing the announcement - Boulland, Romain; Dessaint, Olivier (Journal of Banking & Finance, 2017)
What drives investors’ attention? We study how far in advance earnings calendars are pre-announced and find that investors are more attentive to earnings news when such details are disclosed well ahead of time. This variation in investors' attention affects short-run and long-run stock returns, thereby creating incentives for firms to strategically pre-announce the report date on short notice when the earnings news is bad. Consistent with this idea, firms pre-announce their report dates well ahead of time when earnings are good and do it at the very last moment when earnings are bad. A trading strategy that exploits such variations yields abnormal returns of 1.5% per month.